Prolidase deficiency - Masood Qazi; Bhatt Taseer; Hassan Iffat; Sameen Farah; Majid Sabiya (Wolters Kluwer Medknow Publications, 2007)
Prolidase deficiency is a rare inborn disorder of collagen metabolism characterized by chronic recurrent skin ulceration. A seven-year-old girl and her younger sibling with clinical features and laboratory criteria fulfilling the diagnosis of prolidase deficiency are presented in view of rarity of the condition.